Sensor Selection for Air Quality Monitoring: Machine Learning-Based Calibration and Performance Comparison of IoT Devices for Gaseous Pollutant Elements - K. Ahuja, Kavita (International Journal of Computer Sciences and Engineering, 2025)
Air pollution is becoming a serious problem in cities, with direct impacts on both public health and the environment. Being able to predict the Air Quality Index (AQI) accurately and on time is important for taking steps to prevent or reduce pollution. This study explores the use of IoT-based gas sensors to help forecast AQI, focusing on four main pollutants: Carbon Monoxide (CO), Sulfur Dioxide (SO?), Nitrogen Dioxide (NO?), and Ammonia (NH?). Three different sensors were tested for each gas to see how well they performed. After calibrating the sensors, their readings were converted to parts per million (ppm), and artificial data was created to represent three months of half-hourly readings. A machine learning method, Random Forest Regressor, was used to check how accurate each sensor was, based on performance measures like MAE, RMSE, and R² Score. Sensor, referred as Sensor S1, gave the best results across all gases, showing better accuracy and reliability than the others. This research shows how important it is to choose and calibrate the right sensors for monitoring air quality and could help build better systems for predicting AQI in real time. The findings offer useful information for improving environmental monitoring with smart technology.